Integrating Generative Artificial Intelligence in Higher Education: Opportunities, Challenges, and Pedagogical Implications - Sabri Zulkifli; Zulfahmi; M. Bayu Wibawa (IJNMT (International Journal of New Media Technology), 2026)
The increasing use of digital technology has changed many aspects of higher education, particularly in teaching and learning activities. In recent years, Generative Artificial Intelligence (GenAI) has attracted considerable attention because of its ability to generate content and assist various academic tasks. This study examines the role of GenAI in supporting learning transformation in higher education, focusing on its benefits, challenges, and broader educational implications. A qualitative approach was applied through a literature review of recent scholarly publications related to artificial intelligence in education. The findings suggest that GenAI can improve learning efficiency, support more adaptive and personalized learning experiences, and assist students in academic activities such as research and writing. At the same time, several concerns remain important, including academic integrity, excessive dependence on technology, and the absence of clear institutional regulations. The study also indicates that the successful use of GenAI depends not only on technological capability but also on pedagogical readiness and institutional support. Overall, GenAI offers significant opportunities for higher education; however, its implementation should be managed carefully to ensure that technological innovation remains aligned with ethical and educational values.